Controle democrático e intersetorialidade no Conselho Municipal de Assistência Social na cidade do Rio de Janeiro: construção de uma esfera pública e democrática? - Yaakoub, Melissa Cavalcanti (2006)
The aim of this dissertation was is to analyze, in the political at social assistance, as the practice of democratic control and the intersectorial present itself in direction to construction of a democratic and public sphere. Of that, we have as base the space of Conselho Municipal de Assistência Social do Rio de Janeiro, apprehending as occur the social relations. Thus, verified if the exercise of democratic control is realized and as the intersectorial is present in the social assistance municipal politic. This is a qualitative study based on data collection and analysis from interviews. This analyze of CMAS-RJ integrate the social assistance municipal politic. Like this, to observe the dialogue in this space observing as the democratic and public sphere is constituted. The council is one element the public sphere and alone don´t materialize this sphere.